Purpura fulminans secondary to rickettsial infections: A case series - Saloni Katoch; Ravindra Kallappa; Murugesh B Shamanur; Sneha Gandhi (Wolters Kluwer Medknow Publications, 2016)
Purpura fulminans (PF) is a descriptive term used to describe a heterogeneous group of disorders characterized by rapidly progressive purpuric lesions that may develop into extensive areas of skin necrosis, and peripheral gangrene. This rare disorder is associated with laboratory evidence of consumptive coagulopathy and is often fatal. PF is usually associated with many infections, most notably with meningococcal, staphylococcal, and streptococcal infections. However, there are very few reports of this entity with spotted fever and scrub typhus from India. Rickettsial infections are an underdiagnosed group of diseases presenting as acute febrile illness, with high mortality in untreated cases. Of the available tests, Weil-Felix is a handy and economical tool for early diagnosis of this fatal disease especially in resource poor settings. We present four infants with PF secondary to rickettsial fever diagnosed by the Weil-Felix test.